Unfolding chromosomal uniqueness of the Scilloid ornamental Albuca virens by application of EMA based Giemsa- DAPI staining - Biplab Kumar Bhowmick; Sayani Nag (Caryologia, 2023)
The cytogenetic features in the tribe Ornithogaleae of subfamily Scilloideae is a prerequisite for understanding genome evolution. Unfortunately, genomic or the foundational chromosomal features are neglected within majority of Ornithogaloids, incuding Albuca, one of the largest genus of the tribe. Albuca virens (Lindl.) J.C. Manning & Goldblatt is the only ornamental species of Albuca found to be exotic to India. Analysis of karyotype by EMA method followed by Giemsa and DAPI staining is the first step towards molecular cytogenetics attempted in this species and has currently brought significant resolution in chromosome morphology (especially NORs). The Indian population of A. virens with 2n=6 chromosomes, symmetric karyotype and heterophorphy of NORs provide excellent scope to navigate questions on dysploid origin of Albuca. The regular meiotic stages advocate genomic stability despite vegetative propagation and polysomaty in root cells. The comparative review of chromosomal evolution within Albuca has been discussed in relation to the Indian A. virens as a prototype.